A bottom‐up framework for nurses' protocol‐based care decision‐making - Monica Vázquez‐Calatayud; María J. Pumar‐Méndez; Cristina Oroviogoicoechea (Wiley, 2024)
Abstract Aim To develop a conceptual framework for nurses' protocol‐based care decision‐making. Design Miles & Huberman's bottom‐up approach to developing conceptual frameworks was followed, using data collected from a multiple embedded case study examining protocol‐based decision‐making by nurses in three hospital wards within a university hospital in northern Spain. Methods The qualitative data from the case study, obtained through documentary analysis, observations, and interviews, underwent a secondary analysis consisting of four steps: data reduction, data display, comparison, and drawing conclusions. Results The framework for protocol‐based care decision‐making comprises four components: (1) protocol‐based care, as a balance between standardisation and individualised care, (2) the process, (3) the context, and (4) the elements of protocol‐based care decision‐making. These components and their relationship as a context‐dependent, linear, variable and multifactorial process, directly influenced by the perception of risk, are described and illustrated. Conclusions This study provides a rigorous bottom‐up framework for nurses' protocol‐based care decision‐making. The framework could be a valuable resource for managers, clinical nurses, educators, and researchers to guide and evaluate nurses' decision‐making, leading to improved care quality and reduced variability in clinical practice. Furthermore, the framework lays a foundation for further research and practical applications. Impact This study addressed the problem of understanding nurses' protocol‐based care decision‐making and the need for a specific conceptual framework. The main findings of the study contribute to the development of a rigorous bottom‐up framework comprising four components of protocol‐based care decision‐making. The framework has the potential to improve care quality, reduce variability, enhance patient safety, and increase healthcare efficiency by guiding nurses' decision‐making in various healthcare settings. No Patient or Public Contribution Patient or public contribution was not applicable since the study focused on nurses' decision making.